Effect of Sodium Hydroxide and Sodium Hypochlorite on the Physicochemical Characteristics of Jack Bean Skin (Canavalia ensiformis) - Aurelia, Chrysanta; Murdiati, Agnes; Supriyanto; Ningrum, Andriati (Pakistan Journal of Nutrition, 2019)
Background and Objective: Jack beans are one of the most underutilized legumes in Indonesia and they are rich in protein. In Indonesia, several traditional products have been developed using jack beans as the raw material but the skin is not used, even though it contains dietary fiber, e.g., cellulose, that can be beneficial to human health. The valorization concept is a trending topic that uses byproducts, such as jack bean skin, to increase the value of the raw material. The objective of this research was to investigate the effects of the concentrations of sodium hydroxide (NaOH) and sodium hypochlorite (NaOCl) on several physicochemical characterizations of cellulose from jack bean skin. Materials and Methods: Cellulose isolation was carried out by delignification using NaOH at several concentrations (4, 6, 8, 10 and 20% NaOH), oxidation bleaching using NaOCl at different concentrations (0, 3 and 6% NaOCl) and reduction bleaching using 3% sodium bisulfite. The isolated cellulose from jack bean skins was analyzed and its physicochemical characteristics, e.g., yield, cellulose content, color (lightness), water holding capacity and oil holding capacity, were examined. Then, jack bean skin cellulose was analyzed to determine its functional groups using Fourier transform infrared (FT-IR) spectroscopy. Results: The highest yield of cellulose (46.40%) was obtained by using 4% NaOH. The highest cellulose content [76.79% (%db)] was obtained by using 10% NaOH. Increasing the NaOCl concentration helped lighten the cellulose color. Conclusion: The optimal sample treatment consisted of a combination of 10% NaOH and 3% NaOCl to produce a high cellulose content, light cellulose color and FT-IR peaks similar to commercial cellulose.